Health equity in COVID-19 testing among patients of a large national pharmacy chain - Singh, Tanya; Smith-Ray, Renae L.; Ogunkoya, Elijah; Shah, Amy; Harris, Daniel A.; Hayes, Kaleen N.; Mor, Vincent (Frontiers in Public Health, 2024)
This study utilized COVID-19 testing data from Walgreens, one of the largest community pharmacy chains in the United States. Analysis of over 18 million tests revealed that Black, Hispanic, Latino, and Native American individuals were more likely to test positive for COVID-19 compared to White individuals. Non-White individuals were also more likely to test positive for variants of concern when dominant viral strains were changing in the population (e.g., transition from delta to omicron). This study demonstrates the potential and capacity for large community pharmacy chains to administer, store, and analyze large amounts of COVID-19 testing data to monitor population health and health equity.